GAMBARAN JAMUR DERMATOPYTA PADA HELM OJEK ONLINE DI KECAMATAN KOTA SELATAN KOTA GORONTALO - Suciyanti N. Tayeb; Yolan Dunggio; Muh. Rizman Naim (LPPM Universitas Bina Mandiri Gorontalo, 2022)
Dermatophyta is a group of fungi that cause diseases of the skin that attack keratin parts such as the hair. Tinea capitis is a scalp disorder caused by the fungus Dermatophyta of the genus Trichopyton and Microsporum . This study aims to determine the results of examination of dermatopyta fungi on online motorcycle taxi helmets in Kota Selatan District, Gorontalo City. The method in this study used a qualitative approach, namely examination of dermatopyta fungi on online motorcycle taxi helmets for each inspection method . The type of research in this research is descriptive observational research . The results showed that from examining 10 samples on online motorcycle taxi helmets, it was found that 8 samples (80%) were positive for fungus and 2 samples (20%) were negative for Dermatophyta fungus . The 8 samples examined were not from Dermatophyta fungi . The types of fungi found in 8 samples were Rhizopus Sp 2 samples (20%), Aspergillus niger 3 samples (30%), Aspergillus fumigatus 3 samples (30%) and Aspergillus oryzae 2 samples (20%).